Staphylococcus aureus Multiplexes Death-Effector Deoxyribonucleosides to Neutralize Phagocytes - Eshraq Tantawy; Eshraq Tantawy; Nicoletta Schwermann; Nicoletta Schwermann; Tjorven Ostermeier; Tjorven Ostermeier; Annette Garbe; Heike Bähre; Marius Vital; Volker Winstel; Volker Winstel (Frontiers in Immunology, 2022)
Adenosine synthase A (AdsA) is a key virulence factor of Staphylococcus aureus, a dangerous microbe that causes fatal diseases in humans. Together with staphylococcal nuclease, AdsA generates deoxyadenosine (dAdo) from neutrophil extracellular DNA traps thereby igniting caspase-3-dependent cell death in host immune cells that aim at penetrating infectious foci. Powered by a multi-technological approach, we here illustrate that the enzymatic activity of AdsA in abscess-mimicking microenvironments is not restricted to the biogenesis of dAdo but rather comprises excessive biosynthesis of deoxyguanosine (dGuo), a cytotoxic deoxyribonucleoside generated by S. aureus to eradicate macrophages of human and animal origin. Based on a genome-wide CRISPR-Cas9 knock-out screen, we further demonstrate that dGuo-induced cytotoxicity in phagocytes involves targeting of the mammalian purine salvage pathway-apoptosis axis, a signaling cascade that is concomitantly stimulated by staphylococcal dAdo. Strikingly, synchronous targeting of this route by AdsA-derived dGuo and dAdo boosts macrophage cell death, indicating that S. aureus multiplexes death-effector deoxyribonucleosides to maximize intra-host survival. Overall, these data provide unique insights into the cunning lifestyle of a deadly pathogen and may help to design therapeutic intervention strategies to combat multidrug-resistant staphylococci.